SUSTAINABILITY FACTORS OF SCIENCE PARKS AND RESEARCH CENTRES IN RELATION TO REDUCING IMBALANCE IN EUROPEAN RESEARCH AREA - Hadzima, Branislav; Sedivy, Stefan; Pepucha, Lubomir; Ingrid, Zuziakova (European Scientific Journal, ESJ, 2015)
Direct application of research centres operational models for their sustainability after the financial support from structural funds ends (e.g. after 2015) represents important issue for their managers. How to implement said models cause enormous discussions well ahead of its time. Time lead of such discussion shows that the issue is not really solved. It is necessary to connect sustainability assurance with an active approach to the actual and predictor risk by following the most important goal – reducing imbalance within European research area while ensuring all-society contribution.